DELIVERY CRITERION–BASED AUDITING SYSTEM AT TWO HEALTH FACILITIES IN ERBIL CITY-IRAQ - Raof, Awring Maroof; AL-Hadithi, Tariq Salman; Al-Tawil, Namir Gh. (Journal of Sulaimani Medical College, 2012)
Background Criterion based audits of medical care and services have developed over the last 15 years. Criterion based audit is a well- known approach or tool for improving the quality of care in maternal units. Objective The aim of this study was to assess the quality of care provided for normal deliveries in Erbil city, Iraq. Methods The study extended from 1st of April to the 30th of June 2009. A total of 1299 normal and 120 complicated birth records from the Maternity Teaching Hospital and Mala-Afandy Health Center were reviewed. The WHO questionnaire on Safe Motherhood Needs Assessment was adapted for this study. An initial assessment of the current practice was made by collecting information on five monitoring procedures or criteria (vaginal examin ation, fetal heart monitoring, blood pressure monitoring, birth weight measurement, and assessment of the condition of the newborn) then it was compared to the standard (norm). Results Vaginal examination, fetal heart monitoring, blood pressure measurement and birth weight were recorded in 92.8%, 98.8%, 97.1% and 96.7% of total records, respectively. Substandard practices for vaginal examination, fetal heart monitoring, and blood pressure measurement were 69.6%, 45.4%, and 68.7% respectively. Partograph forms were available in labour rooms, but they were not in use. Assessment of the condition of newborn was not recorded. Conclusion The overall quality of care was poor with no use of partography. There is a need for development of clinical guidelines and protocols.
Keywords: Auditing; Partograph; Substandard practices